A joint analysis using exome and transcriptome data identifiescandidate polymorphisms and genes involved with umbilical hernia in pigs - Savoldi I.R.* (2021)
© 2021, The Author(s).Background: Umbilical Hernia (UH) is characterized by the passage of part of the intestine through the umbilical canal forming the herniary sac. There are several potential causes that can lead to the umbilical hernia such as bacterial infections, management conditions and genetic factors. Since the genetic components involved with UH are poorly understood, this study aimed to identify polymorphisms and genes associated with the manifestation of umbilical hernia in pigs using exome and transcriptome sequencing in a case and control design. Results: In the exome sequencing, 119 variants located in 58 genes were identified differing between normal and UH-affected pigs, and in the umbilical ring transcriptome, 46 variants were identified, located in 27 genes. Comparing the two methodologies, we obtained 34 concordant variants between the exome and transcriptome analyses, which were located in 17 genes, distributed in 64 biological processes (BP). Among the BP involved with UH it is possible to highlight cell adhesion, cell junction regulation, embryonic morphogenesis, ion transport, muscle contraction, within others. Conclusions: We have generated the first exome sequencing related to normal and umbilical hernia-affected pigs, which allowed us to identify several variants possibly involved with this disorder. Many of those variants present in the DNA were confirmed with the RNA-Seq results. The combination of both exome and transcriptome sequencing approaches allowed us to better understand the complex molecular mechanisms underlying UH in pigs and possibly in other mammals, including humans. Some variants found in genes and other regulatory regions are highlighted as strong candidates to the development of UH in pigs and should be further investigated.